1999
DOI: 10.1080/02724939992482
|View full text |Cite
|
Sign up to set email alerts
|

Sydenham's chorea: risk factors and the role of prophylactic benzathine penicillin G in preventing recurrence

Abstract: To determine the effect of prophylactic long-acting penicillin G in preventing recurrence of Sydenham's chorea and to discover the risk factors associated with occurrence of symptoms, 18 children with symptoms over a 5-year period were prospectively identified. Of these, ten were boys and eight were girls. The majority occurred between the ages of 8 and 10 years [mean (SD) 9.10 (2.62) years]. Sydenham's chorea was generalized in 14 children and one-sided in four. There was no difference in the incidence of rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…By examining the scant literature on using antibiotics to prevent SC recurrences, the complications in determining efficacy become apparent. Although prophylactic antibiotic therapy in patients with SC appears successful in the prevention of neuropsychiatric exacerbations (Gebremariam 1999), other investigators report that about a third will continue to have a recurrence (Terreri et al 2002). Studies in which SC patients received monthly prophylactic injections of benzathine penicillin G showed that not all SC recurrences appear to be GAS triggered (Korn-Lubetzki et al 2004) and that recurrences may occur after infections that are too mild or too brief to be easily detected (Berrios et al 1985).…”
Section: Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…By examining the scant literature on using antibiotics to prevent SC recurrences, the complications in determining efficacy become apparent. Although prophylactic antibiotic therapy in patients with SC appears successful in the prevention of neuropsychiatric exacerbations (Gebremariam 1999), other investigators report that about a third will continue to have a recurrence (Terreri et al 2002). Studies in which SC patients received monthly prophylactic injections of benzathine penicillin G showed that not all SC recurrences appear to be GAS triggered (Korn-Lubetzki et al 2004) and that recurrences may occur after infections that are too mild or too brief to be easily detected (Berrios et al 1985).…”
Section: Antibioticsmentioning
confidence: 99%
“…These studies suggest that some improvement in the course occurs after prophylactic antibiotics, however, the sample sizes were small, all were open label, and most patients with SC take prophylactic antibiotics until their late teens. Consequently, data exist to compare overall neuropsychiatric severity of those receiving treatment with those who do not (Gebremariam 1999).…”
Section: Antibioticsmentioning
confidence: 99%
“…• One retrospective study looked at the recurrence risk in 18 patients with SC who received monthly intramuscular penicillin versus a historical cohort of 23 patients with SC who were never placed on penicillin prophylaxis. None of the patients who were on prophylactic penicillin had recurrence of chorea, whereas recurrences occurred in 10 of the 23 patients who did not receive penicillin [40]. Time to recurrence varied between 8 months and 30 years in the historical cohort.…”
Section: Multiple Pharmacologic Therapiesmentioning
confidence: 91%
“…Secondary prophylaxis with penicillin has been shown to help prevent the recurrence of chorea [40,Class III]. In children with a diagnosis of SC without valvular heart disease, penicillin, that is, monthly intramuscular penicillin G or twice-daily oral penicillin V, is recommended for 5 years or until age 21, whichever period is longer [40][41][42]. Doses are 1,200,000 U of intramuscular benzathine penicillin G every 4 weeks or oral penicillin V 250 mg twice per day.…”
Section: Multiple Pharmacologic Therapiesmentioning
confidence: 99%
See 1 more Smart Citation